Optimal Enforcement Policy and Firms' Emissions and Compliance with Environmental Taxes - Ines Macho-Stadler; David Pérez-Castrillo (Center for Economic Studies and ifo Institute (CESifo), 2004)
In a market where firms with different characteristics decide upon both the level of emissions and their reports, we study the optimal audit policy for an enforcement agency whose objective is to minimize the level of emissions. We show that it is optimal to devote the resources primarily to the easiest-to-monitor firms and to those firms that value pollution the less. Moreover, unless the budget for monitoring is very large, there are always firms that do not comply with the environmental objective and others that do comply; but all of them evade the environmental taxes.
Keywords: 330; environmental taxes; optimal audit policy